2019
DOI: 10.1002/lary.27535
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric dysphagia: Is interarytenoid mucosal height significant?

Abstract: Objectives: The clinical significance of the interarytenoid mucosal height (IAMH) in pediatric dysphagia, ranging from normal anatomy to a laryngeal cleft, is unknown. This study seeks to evaluate a cohort of patients who underwent evaluation of their IAMH during microdirect laryngoscopy (MDL) for associations between IAMH and dysphagia as diagnosed on preoperative videofluoroscopic swallow study (VFSS).Methods: A retrospective case series of 1,351 patients who underwent MDL between 2011 and 2016 were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Within our cohort we found 4.85% of patients to have a laryngeal cleft at the level of the TVF based on our current working definition, which is consistent with previous studies 29 . In addition, we affirmed previous studies which noted that patients with normal anatomy can present with pharyngeal dysphagia 25 and can significantly benefit in terms of advancing diet consistency by reducing aspiration risk with IAIA, 24 as our study was comprised mostly (53.4%) of patients with normal IAMH (above the level of the FVF).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Within our cohort we found 4.85% of patients to have a laryngeal cleft at the level of the TVF based on our current working definition, which is consistent with previous studies 29 . In addition, we affirmed previous studies which noted that patients with normal anatomy can present with pharyngeal dysphagia 25 and can significantly benefit in terms of advancing diet consistency by reducing aspiration risk with IAIA, 24 as our study was comprised mostly (53.4%) of patients with normal IAMH (above the level of the FVF).…”
Section: Discussionsupporting
confidence: 92%
“…24 Additional studies since have shown no correlation between interarytenoid mucosal height (IAMH) and dysphagia symptoms. 25 This poses an ambiguous clinical scenario in which our current consensus statements do not help guide clinicians caring for patients with normal interarytenoid anatomy and dysphagia given the results of these studies.…”
Section: Introductionmentioning
confidence: 93%
“…Additionally, some authors have argued that augmentation of the posterior larynx can improve clinical aspiration and SD even without definitive evidence of an anatomic cleft [16], as well as in the setting of a 'deep inter-arytenoid notch.' [17] One recent study attempted to measure the mucosal height of the posterior inter-arytenoid space and correlate this with the need for thickened feeds however no significant association was found [18]. In our experience, a blend of anatomic and functional cleft approaches serves the clinician best.…”
Section: Discussionmentioning
confidence: 79%
“…Patients with pharyngeal dysphagia and those with type I laryngeal cleft have been shown to benefit from IAIA 11,12 . Recent data suggest that the interarytenoid mucosal height may not necessarily correlate with presence or absence of dysphagia as even patients without a true type I laryngeal cleft who exhibit pharyngeal dysphagia can advance their diet after IAIA 13, 14 …”
Section: Discussionmentioning
confidence: 99%